2011
DOI: 10.1002/jcc.21778
|View full text |Cite
|
Sign up to set email alerts
|

Web services as applications' integration tool: QikProp case study

Abstract: Web services are a new technology that enables to integrate applications running on different platforms by using primarily XML to enable communication among different computers over the Internet. Large number of applications was designed as stand alone systems before the concept of Web services was introduced and it is a challenge to integrate them into larger computational networks. A generally applicable method of wrapping stand alone applications into Web services was developed and is described. To test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…QikProp is an ADME program offered by Schrodinger that predicts pharmaceutically relevant and physically significant descriptors for small drug-like molecules [232]. The VolSurf package can be used to calculate ADME properties and generate ADME models [233].…”
Section: Reviewmentioning
confidence: 99%
“…QikProp is an ADME program offered by Schrodinger that predicts pharmaceutically relevant and physically significant descriptors for small drug-like molecules [232]. The VolSurf package can be used to calculate ADME properties and generate ADME models [233].…”
Section: Reviewmentioning
confidence: 99%
“…The remaining six hundred structures (600) were then evaluated for their pharmacokinetic properties (the absorption, distribution, metabolism) using the QikProp software [ 37 , 38 , 39 ]. Structures submitted for pharmacokinetic study, resulted in two hundred and thirty-three (233) hits that presented satisfactory pharmacokinetic properties, especially electronic affinity, Lipinski’s rule, and the central nervous system (CNS) parameter, when compared with the properties of Rofecoxib.…”
Section: Resultsmentioning
confidence: 99%
“…Several reviews have focused on previously reported resources, specifically, publicly available databases with ADMET‐related content and software and tools for ADMET‐related property prediction . As the data and models have aggregated, many prediction tools have been integrated into comprehensive commercial software, such as QikProp (http://www.schrodinger.com/QikProp/) and VolSurf+ (http://www.moldiscovery.com/software/vsplas/). In addition, some academic institutions have also developed free comprehensive ADMET software or have provided online services, such as PK/DB, admetSAR, pkCSM and FAF‐Drugs4 .…”
Section: Computational Methods For Cbddmentioning
confidence: 99%